A woman, a gun and a noodle shop [videorecording (DVD)] - Sun, Honglei; Xiaoshenyang, 1981-; Yan, Ni, 1971- (Sony Pictures Home Entertainment, 2011)
When an older, abusive husband discovers his younger wife is having an affair, he devises a scheme to murder her. This sets off a series of revengeful activities.